Hepcidin and Anemia: A Tight Relationship - Pagani, Alessia; Nai, Antonella; Silvestri, Laura; Camaschella, Clara (Frontiers in Physiology, 2019)
Hepcidin, the master regulator of systemic iron homeostasis, tightly influences erythrocyte production. High hepcidin levels block intestinal iron absorption and macrophage iron recycling, causing iron restricted erythropoiesis and anemia. Low hepcidin levels favor bone marrow iron supply for hemoglobin synthesis and red blood cells production. Expanded erythropoiesis, as after hemorrhage or erythropoietin treatment, blocks hepcidin through an acute reduction of transferrin saturation and the release of the erythroblast hormone and hepcidin inhibitor erythroferrone. Quantitatively reduced erythropoiesis, limiting iron consumption, increases transferrin saturation and stimulates hepcidin transcription. Deregulation of hepcidin synthesis is associated with anemia in three conditions: iron refractory iron deficiency anemia (IRIDA), the common anemia of acute and chronic inflammatory disorders and the extremely rare hepcidin-producing adenomas that may develop in the liver of children with an inborn error of glucose metabolism. Inappropriately high levels of hepcidin cause iron-restricted or even -deficient erythropoiesis in all these conditions. Patients with IRIDA or anemia of inflammation do not respond to oral iron supplementation and show a delayed or partial response to intravenous iron. In hepcidin producing adenomas anemia is reverted by surgery. Other hepcidin-related anemias are the “iron loading anemias” characterized by ineffective erythropoiesis and hepcidin suppression. This group of anemias includes thalassemia syndromes, congenital dyserythropoietic anemias, congenital sideroblastic anemias and some forms of hemolytic anemias as pyruvate kinase deficiency. The paradigm is non-transfusion-dependent-thalassemia where the release of erythroferrone from the expanded pool of immature erythroid cells results in hepcidin suppression and secondary iron overload that in turn worsens ineffective erythropoiesis and anemia. In thalassemia murine models approaches that induce iron restriction ameliorate both anemia and the iron phenotype. Manipulations of hepcidin might benefit all the above-described anemias. Compounds that antagonize hepcidin or its effect may be useful in inflammation and IRIDA, while hepcidin agonists may improve ineffective erythropoiesis. Correcting ineffective erythropoiesis in animal models ameliorates not only anemia but also iron homeostasis by reducing hepcidin inhibition. Some targeted approaches are now in clinical trials: hopefully they will result in novel treatments for a variety of anemias.